Improving Badminton Learning Outcomes Using Bokortasko Tool Modifications - Munha, Mohammad Alhadi; Usra, Meirizal; Destriani, Destriani (Altius: Jurnal Ilmu Olahraga dan Kesehatan, 2023)
This study aims to improve the learning outcomes of badminton students by using bokortasko tools. This research is a collaborative classroom action research with four stage steps, namely planning, implementation, observation and reflection. In this research is carried out through the stages of pre-cycle, cycle 1 and cycle 2. In the pre-cycle skill test scores were 47.40% (low), learning outcomes were 20.58% (complete), and affective students were 49.99% (less active). In the first cycle the skill test score was 63.39% (moderate), the learning outcomes were 64.71% (complete), and the affective students were 62.65% (quite active). And in cycle II skill test scores of 82.88% (high), learning outcomes of 85.29% (complete), and affective students 82.70% (very active). So it can be concluded through the modification of bokortasko aids can improve stud ent learning outcomes, this can be seen from the actions carried out each cycle has increased significantly and the use of bokortasko aids can help students learn and practice service techniques and lob strokes so that they have an impact on student learning success.